3x(2)+8x-3=0

Simple and best practice solution for 3x(2)+8x-3=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x(2)+8x-3=0 equation:



3x(2)+8x-3=0
We add all the numbers together, and all the variables
3x^2+8x-3=0
a = 3; b = 8; c = -3;
Δ = b2-4ac
Δ = 82-4·3·(-3)
Δ = 100
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{100}=10$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(8)-10}{2*3}=\frac{-18}{6} =-3 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(8)+10}{2*3}=\frac{2}{6} =1/3 $

See similar equations:

| 20+8x=10x | | 4c-10c=5 | | (1.51^x)=65 | | x^2-9x-21=0 | | 5x+3=2x+6 | | 3(60+x)=5x | | 6x+7=23x= | | -2(t–4)=8 | | 0.571y-2=0.429y+0.214 | | c–14=-12 | | -2(b+13)=-20 | | 640000/8000=n | | 7x-5x=210 | | 7(v+2)=4v+44 | | X=-0.5y+0.757 | | 7x+4=11+2x. | | 2x+15=1x+25 | | 2(x-2)+3=8(x-6) | | 6+6+1/3x=x | | X20=3x | | 1(x-1)-7=5(x+3) | | -7x+12—2x=23+13x | | 2(x-6)+7=1(x+5) | | -2(x+5)=-7(x-6)+5x | | 29=41-5(-3-4w) | | -7(6x+7)-3=-42x-50 | | 3(3y+1)=-35 | | 1+x=3-3x | | 3x/5=(-6) | | 4x-11=-20x+1 | | 2x^2-0.2x-0.01=0 | | 3x-8=11x-19 |

Equations solver categories